2019
DOI: 10.1097/btf.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Nontraditional Dual Incision Approach for Lisfranc Trauma, Fractures, and Osteoarthritis

Abstract: Background: Numerous surgical approaches and treatments for Lisfranc pathology have been described and vary across physicians and surgical specialties. Many incisions to access the tarsometatarsal (TMT) joint complex have been described including single and dual longitudinal as well as transverse. The aim of this study was to retrospectively review and compare complication and fusion rates in patients with a Lisfranc open reduction and internal fixation or arthrodesis utilizing a nontraditional dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…11,12 This dogma has been challenged in recent years, with reviews of the literature showing good reported outcomes for case series using multiple incisions, <7 cm apart, for pilon fractures, calcaneal osteotomies, and LisFranc injuries. [13][14][15] Our hypothesis was that by having a careful attitude toward soft tissue swelling and wound care, we would be able From the *St. James Hospital Dublin, Dublin; and †Midland Regional Hospital Tullamore, Tullamore, Ireland. The authors declare no conflict of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 This dogma has been challenged in recent years, with reviews of the literature showing good reported outcomes for case series using multiple incisions, <7 cm apart, for pilon fractures, calcaneal osteotomies, and LisFranc injuries. [13][14][15] Our hypothesis was that by having a careful attitude toward soft tissue swelling and wound care, we would be able From the *St. James Hospital Dublin, Dublin; and †Midland Regional Hospital Tullamore, Tullamore, Ireland. The authors declare no conflict of interest.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely cited for many years that there should be a 7 cm skin bridge between incisions around the foot and ankle, though a review of the literature does not show where this figure was derived from 11,12. This dogma has been challenged in recent years, with reviews of the literature showing good reported outcomes for case series using multiple incisions, <7 cm apart, for pilon fractures, calcaneal osteotomies, and LisFranc injuries 13–15…”
Section: Introductionmentioning
confidence: 99%